Persepsi pemustaka terhadap edukasi plagiarisme melalui media sosial: Studi kualitatif feed di Instagram Perpustakaan Afiyo - Muhammad Luthfy Ihsan; Labibah Zain (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2025)
The use of the AFIYO Library Instagram feed as a medium for plagiarism education is the focus of this study, with the aim of exploring the perceptions and impact of library users on plagiarism education content. With the increasing number of plagiarism cases in academic environments, this study aims to assess the effectiveness of the visual design of the Instagram feed in conveying messages about writing ethics. The method used is qualitative research with a descriptive approach. Primary data was collected through in-depth interviews with seven active library users at the AFIYO Library, while secondary data was obtained from literature reviews related to information literacy and social media content design. Data analysis was conducted thematically to identify patterns of perception and attitude changes. The main results indicate that the combination of neutral gray colors, Montserrat and Agrandir typography, minimalist illustrations, and consistent layout makes plagiarism education content easy to understand and attention-grabbing. Most informants stated that the concise presentation and harmonious visuals made it easier for them to understand the types of plagiarism and the importance of citations. A total of 87.5% of respondents reported an increase in ethical awareness, and 37.5% actively shared the content with their peers. Discussions revealed that the credibility of the library account strengthened user trust, making educational messages easier to absorb and internalize. The summary of findings emphasizes that the use of the AFIYO Library's Instagram feed significantly contributes to improving plagiarism literacy among students. The implications of this study include recommendations for academic libraries to optimize social media as an educational tool, as well as suggestions for further research on comparing the effectiveness of other platforms and evaluating the long-term impact of digital education campaigns.